THE APPLICATION THINK TALK WRITE LEARNING MODEL TO IMPROVE COMPOSING SHORT STORIES - Lisbet Hutabarat (Hortatori : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2020)
Abstract: This study aims to apply the think talk write learning model to improve Indonesianlearning outcomes in composing short stories in Class IX.1 SMP Negeri 10 Kota Bekasi. Thesubjects were students of class IX.1 SMP Negeri 10 Kota Bekasi total of 40 students. The method usedwas classroom action research. Methods of data collection using tests, observations, interview, anddocumentation. The results obtained by the test result data evaluation of learning that have increasedeach cycle, the test results obtained pre-cycle average value of 73,30 with mastery learning 47,50%,which has increased in the cycle I average value of 78,55 with mastery learning 72,50%, which hasincreased in the cycle II average value of 81,10 with mastery learning 92,50%. The conclusion of thisstudy is through the learning model of think talk write can improve Indonesian learning outcomessubject of compile short stories in class IX.1 SMP Negeri 10 Kota BekasiKey Words: Indonesian Language, Short Story, Think Talk Write